Impact of acute weight loss and/or thermal stress on rowing ergometer performance - Slater, G. J.; Rice, A. J.; Sharpe, K.; Tanner, R.; Jenkins, D.; Gore, C. J.; Hahn, A. G. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The impact of acute weight loss on rowing performance was assessed when generous nutrient intake was provided in 2 h of recovery after making weight.